Nanotechnology applications: the future arrived suddenly - Ferreira, M. A. M.; Filipe, J. A. (Computational approaches in biomedical nano-engineering, 2018)
There is already a significant time, but it gives the sensation of an extremely short period – nanotechnology has become one of the most promising scientific hopes in innumerable human domains. Now the hope became reality. Countless scientific studies in several areas of knowledge have been made since the nanoscale emergence, carrying their contribution to the nanoscience development. The recent researches in this field allowed the union of interests among several areas, such as physical sciences, molecular engineering, biology, biotechnology, and medicine, contributing to the investigation of biosystems at a nanoscale. This chapter begins by discussing nanotechnology in a general way. Then nanotechnology and its applications in industry, in electronics, and in medicine are presented, and some discussion is proposed in order to define the boundaries for the advances in those areas. In the end, nanotechnology is discussed in terms of ethics and the borders that nanotechnology applications must satisfy, and concluding notes are presented, highlighting the results of the analysis. Important considerations are made about the close connection between ethics and the nanotechnology and the effects over the society and values. Some future directions for the research are suggested.